Development of a Microcontroller-Based Clean Bilge System Prototype with Power Monitoring for Community Empowerment - Yoga Bagus Nugraha (Politeknik Perkapalan Negeri Surabaya, 2025)
Oil waste remains a significant contributor to marine pollution, primarily due to a lack of awareness and understanding regarding its proper management. This research focuses on addressing this issue through the development of a microcontroller-based clean bilge system prototype equipped with a power monitoring feature. The study is designed as a community engagement initiative aimed at fostering environmental consciousness and technological literacy among various societal groups. The methodology employs a participatory approach, starting with problem identification to understand the limited knowledge surrounding the importance of bilge systems on ships. Relevant literature on bilge systems and the environmental impacts of oil pollution is reviewed to inform the design of a practical solution. Stakeholders, including students and community members, are actively involved in the research process to ensure that the proposed innovation aligns with real-world needs. The results introduce a compact and user-friendly prototype that replicates the essential functions of a ship's bilge system. The integrated power monitoring system enhances operational efficiency by providing real-time feedback, allowing for immediate resolution of power-related issues. This innovation not only serves as a practical tool for educating communities about sustainable marine practices but also acts as a preventive measure to minimize the environmental harm caused by improper oil waste disposal. This study contributes to community service efforts by bridging the gap between environmental sustainability and technological education. The proposed solution has the potential to inspire further adoption of clean bilge systems and supports broader initiatives in marine conservation and community empowerment.